Studi Kajian Realisasi Belanja Pemerintah Daerah Kabupaten Deli Serdang - Dwi Aulia Putri; Tesalonika Br Tarigan; Marshanda Sylvia; Titah Enjelina Manurung; Rusiadi Rusiadi; Dewi Mahrani Rangkuty (Jurnal Kajian dan Penelitian Umum, 2023)
This study aims to analyze the realization of local government expenditure in Deli Serdang Regency. This type of research is descriptive qualitative with a literature study research method through literature studies related to the title. The results of the research are based on the analysis that the realization of overall government expenditure for 5 (five) years in Deli Serdang Regency has an average of 63.41%, meaning that the performance of the Deli Serdang Regency government is considered good. Where in 2018-2022 the Deli Serdang Regency government used less than 100% of the budgeted amount. However, in terms of the nominal amount of expenditure realization, the Deli Serdang Regency Government has increased, but this amount is still relatively small from the total budget that has been determined so that performance is still considered good and can utilize the expenditure budget not exceeding the budgeted amount.